Pengaruh Social Media Marketing dan Kualitas Produk terhadap Keputusan Pembelian pada Restoran Suis Butcher Setiabudhi - Rina Julianti; Mahani, Septiana Ayu Estri; Rohandi, Mochamad Malik Akbar (Bandung Conference Series: Business and Management, 2024)
Abstract. Currently, restaurants are required to further increase visits and income through sales to maintain and increase competition with their competitors through information provided through social media, as well as providing good raw materials to produce quality products that can influence consumer purchasing decisions. This research aims to understand how Social Media Marketing, Product Quality and Purchasing Decisions at the Suis Butcher Setiabudhi restaurant are, as well as how much influence Social Media Marketing, Product Quality has on Purchasing Decisions partially and simultaneously. This research is a type of descriptive and verification research that uses quantitative methods, with a sampling technique involving 100 consumer respondents who have purchased at the Suis Butcher Setiabudhi restaurant. Data analysis was carried out using descriptive analysis and multiple linear regression with T-test and F-test. And the results of this research show that Social Media Marketing partially has a significant effect on purchasing decisions. Product quality partially has a significant effect on purchasing decisions. Then Social Media Marketing and Product Quality simultaneously influence purchasing decisions. Abstrak. Saat ini restoran dituntut untuk lebih meningkatkan kunjungan serta pendapatan melalui penjualan untuk mempertahankan dan meningkatkan persaingan dengan para pesaingnya melalui informasi yang diberikan melalui sosial media, serta memberikan bahan baku yang baik untuk menghasilkan kualitas produk yang dapat mempengaruhi keputusan pembelian konsumen. Penelitian ini bertujuan untuk memahami bagaimana Social Media Marketing, Kualitas Produk, dan Keputusan Pembelian di restoran Suis Butcher Setiabudhi, serta seberapa besar pengaruh Social Media Marketing, Kualitas Produk terhadap Keputusan Pembelian secara parsial dan simultan. Penelitian ini merupakan jenis penelitian deskriptif dan verifikatif yang menggunakan metode kuantitatif, dengan teknik sampling yang melibatkan 100 responden konsumen yang pernah membeli di restoran Suis Butcher Setiabudhi. Analisis data dilakukan menggunakan analisis deskriptif serta regresi linier berganda dengan pengujian uji-T dan uji-F. Serta hasil penelitian ini menunjukan Social Media Marketing secara parsial berpengaruh signifikan terhadap Keputusan Pembelian. Kualitas Produk secara parsial berpengaruh signifikan terhadap Keputusan Pembelian. Kemudian Social Media Marketing dan Kualitas Produk secara simultan berpengaruh terhadap Keputusan Pembelian.